Profil Status Oksigenasi, Berat Badan dan Lama Rawat Bayi Respiratory Distress Syndrome yang diberikan Air Susu Ibu (ASI) di Ruang Perinatologi - Armina, Armina; Pebrianti, Dwi Kartika (Jurnal Akademika Baiturrahim Jambi, 2024)
Babies born with Respiratory Distress Syndrome (RDS) will experience various health problems. Respiratory Distress Syndrome is an acute and severe lung disease due to surfactant deficiency in infants. Cases of infants with RDS for 8 months in 2022 there were 10 cases every month at Hospital X, Jambi City. The purpose of this study was to determine the health status of infants with RDS who were treated, especially in breastfeeding. This population was infants with RDS who were treated in the Perinatology Room of Hospital X, Jambi City from January to August 2024 and a large sample size of 46 RDS infants. This study uses secondary data from medical records and research instruments in the form of a baby checklist consisting of variables such as age, gender, provision of liquid milk diet, oxygenation status, weight after being given a liquid milk diet and length of hospitalization for RDS babies. Exclusion criteria were infants referred to other hospitals, infants forcibly taken home by their parents, and RDS infants who died. Statistical analysis used Univariate Analysis. The results of the study found that the majority of newborns were over 37 weeks old, male, birth weight over 2,500 grams, diet given in the form of breast milk, respiratory rate after breastfeeding less than 60x/minute, baby weight after breastfeeding more than 2,500 grams and length of stay less than 4 weeks. This study is expected to be a reference in teaching nursing or health and can be used as further research.